Existence of Regional Development Planning Agency (BAPPEDA) in Infrastructure Development Planning in Palopo City - Rahmatang (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Study This discuss about The existence of the Regional Development Planning Agency (BAPPEDA) in Planning for the Development of Infrastructure Facilities in Palopo City . Purpose : Objectives from study This For analyze existence Regional Development Planning Agency in planning development means infrastructure in Palopo City as well as analyze obstacles faced​ Regional Development Planning Agency in planning development means infrastructure in Palopo City . Methods : Research This use type study qualitative . Subject study in study This among others the Head Bappeda , Secretary Bappeda , Head of Economic and Social Affairs , Head of Macroeconomics , and Head of Infrastructure and Regional Development . Taking subject study This done with purposive sampling technique . Data obtained through interviews , observations , documentation and studies bibliography . Furthermore , the technique analysis used​ is collecting data (data collection), data reduction , data presentation and Data verification . Results : Result of study This is existence Regional Development Planning Agency of Palopo City that is do planning , control , implementation , and do evaluation performance . In do its function Bappeda also does coordination with Palopo City Government and related OPDs in matter implementation . In matter planning regional development planning agency create a program based on a number of the later approach will jointly determined by the Palopo City Government and the legislative body . The obstacles faced Regional Development Planning Agency of Palopo City in do planning development that is aspect characteristics of the Palopo City area , applicable regulations , limitations source power , and lack of understanding public related reason Musrenbang No accommodated with good . Implications : Existence Regional Development Planning Agency of Palopo City in achievement his work can measured through the planned program as part from the development program planning process as well as to harmonize with plan Work government region (RKPD) as guidelines in compilation design budget government area (RAPD). It is expected researcher furthermore can do study in detail with use accountability , transparency related task from Regional Development Planning Agency .